Over-allotment options in IPOs on Germany's Neuer Markt: An empirical investigation - Stefanie A. Franzke; Christian Schlag (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
Over-allotment arrangements are nowadays part of almost any initial public offering. The underwriting banks borrow stocks from the previous shareholders to issue more than the initially announced number of shares. This is combined with the option to cover this short position at the issue price. We present empirical evidence on the value of these arrangements to the underwriters of initial public offerings on the Neuer Markt. The over-allotment arrangement is regarded as a portfolio of a long call option and a short position in a forward contract on the stock, which is different from other approaches presented in the literature. Given the economically substantial values for these option-like claims we try to identify benefits to previous shareholders or new investors when the company is using this instrument in the process of going public. Although we carefully control for potential endogeneity problems, we find virtually no evidence for a reduction in underpricing for firms using over-allotment arrangements. Furthermore, we do not find evidence for more pronounced price stabilization activities or better aftermarket performance for firms granting an over-allotment arrangement to the underwriting banks.
urn:nbn:de:hebis:30-10068
Keywords: G32; G13; 330; Over-Allotment Option; Flotation Costs; Underwriter Fee; Neuer Markt